Pengaruh Leverage, Profitabilitas, Capital Intensity, Dan Corporate Governance Terhadap Tax Avoidance - Salsabila, Anina Berliana; Budiman, Judi (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The variables of leverage, profitability, capital intensity, and corporate governance are examined in this research related to tax avoidance. The research uses a quantitative method with an explanatory design. The main focus is primary consumer goods manufacturing companies listed on the Indonesia Stock Exchange (IDX). The purposive sample consists of companies that present complete financial data in rupiah and do not experience losses during the research period. Secondary data are taken from annual reports on the IDX website and the company's official website. The findings show that tax avoidance is negatively and significantly affected by the four variables: profitability, capital intensity, corporate governance, and leverage. The ability to deduct interest from taxable income makes high leverage less attractive as a means of tax avoidance. Financially healthy companies tend to pay taxes correctly, so the incentive to avoid taxes decreases as profits increase. Allowable depreciation helps companies with high capital intensity to avoid having to use aggressive tax strategies. Independent commissioners and audit committees are examples of good governance, increasing transparency and oversight, thereby reducing the possibility of tax avoidance.